Pengaruh Kompetensi Dan Budaya Kerja Terhadap Produktivitas Melalui Kualitas Pelayanan Pegawai Pada Dinas Pekerjaan Umum, Penataan Ruang, Perumahan Dan Kawasan Permukiman Kabupaten Takalar - Mashur Razak; Ahmad Firman; Mulyawan Amin (AkMen JURNAL ILMIAH, 2022)
This research is a quantitative research that uses a survey method with a questionnaire data collection tool. This study aims to determine the effect of competence and work culture on employee productivity through service quality at the Department of Public Works, Spatial Planning, Housing and Settlement Areas of Takalar Regency. The population in this study were employees of the Department of Public Works, Spatial Planning, Housing and Settlement Areas of Takalar Regency, amounting to 79, while the sampling technique was based on the saturated sample method so that the sample obtained was 79 respondents. Data analysis used is path analysis using SmartPls 3.0 software. The results of the study indicate that (1) Competence and work culture have a direct influence on service quality. (2) Competence, work culture, and service quality have a direct influence on employee productivity. (3) Competence and work culture have an indirect influence on employee productivity by being mediated by service quality